Fast SDN updates using tree-based architecture. (5th May 2020) - Hatami, Rashid; Bahramgiri, Hossein
Network updates and configurations in software-defined networking (SDN) are critical and occur frequently. The effectiveness of many systems depends on the speed of adaption to their current workload and updates. Slower updates would reduce network utilisation because during a longer period it can lead to congestion and packet loss. Hence, quickly updating is a challenge in SDN architecture. In this paper, we propose a practical method for implementing a system for fast updates, using tree-based architecture. It can be used to implement the inserting, deleting and modifying rules on the flow-table quickly, and achieves a reduction in the update time. Experimental results show that our design can improve the median update speed.